2021
DOI: 10.32732/jcec.2021.10.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical Behavior of Stabilized Dunes Sand by Cement

Abstract: The dunes sand is wide spread with huge quantities all over the world especially in desert areas near roads. The objective of the current paper is to use dunes sand as a foundation soil under structures instead of utilizing expensive replacement with structural fills. The dunes sand samples were collected from a site outside Tabuk city in the north-west of Saudi Arabia. Several experimental tests were performed on the dunes sand samples such as sieve analysis, standard Proctor compaction, drained direct shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The work outcomes indicated that the bearing capacity of the stabilized sand increases by increasing the cement content, and it is independent of the compaction energy. Elsawy [5] investigated the behavior of dune sand stabilized with different percentages of cement. The results showed that the maximum dry density increases with the increase in cement content leading to a reduction in porosity and optimum moisture content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work outcomes indicated that the bearing capacity of the stabilized sand increases by increasing the cement content, and it is independent of the compaction energy. Elsawy [5] investigated the behavior of dune sand stabilized with different percentages of cement. The results showed that the maximum dry density increases with the increase in cement content leading to a reduction in porosity and optimum moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have indicated that, in the absence of stabilizer in Aeolian sand, Aeolian sand exhibited CBR value of almost 4%. However, incorporating 10% cement and 15% geopolymer resulted in CBR values of 133% and 112%, respectively [5].…”
Section: Introductionmentioning
confidence: 99%